Design, Simulation and Kinematics Analysis of Robot Manipulator with PPRR Joints Configuration - Asmara Yanto; Ahmad Jeni (LP2M - Institut Teknologi Padang, 2019)
This research aims to create an innovation in the design of Robot Manipulator with joint configuration in the form of two prismatic movements and two revolute movements (PPRR), serially. The Robot Manipulator design is validated by performing kinematics simulation and analysis of a trajectory. To simulate the movement of this Robot Manipulator, the end-effector Robot Manipulator is equipped with stationery in the form of a marker to follow the trajectory of the block letters. Robot Manipulator consists of four links. Link-1 moves prismatically on a horizontal linear sliding rail system (LSRS) with a rail length of 450 mm. The center point of Link-1 can move from a position of 75 mm to 375 mm in the X-axis direction. The Y-axis parallel links with a length of 80 mm move prismatically on a vertical linear rail system (LSRS) with a rail length of 60 mm. The conditioned link-2 can move from 140 mm to 180 mm in the direction of the Z-axis. Link-3 revolves in the X-Y plane with a range of 0o to 180o. Link-4 revolves in the X-Y plane with a range of 0o to 180o. From the simulation and kinematics analysis of Robot Manipulator with trajectory in the form of ITP block letters it can be concluded that the Robot Manipulator is indicated to be able to follow the trajectory well.